Efektivitas Kelembagaan Lokal dalam Pengelolaan Sumber Daya Hutan pada Masyarakat Rumahkay di Seram Bagian Barat, Maluku - Syarif Ohorella; Didik Suharjito; Iin Ichwandi (Institut Pertanian Bogor (IPB University), 2011)
Debate on the role of local institution in ensuring natural resources sustainability was re-tested in this research. The local institution in question consisted of kewang, church, and sasi darat (rules) being practiced in the management of dusun (forest) in Rumahkay village. This study described the effectiveness of local institution in the sustainable management of dusun under various types of property rights i.e. dusun dati, dusun negeri, dusun pusaka, and dusun parusahaan. Case study method was used in this research. Data were collected through semi-structured interview, participant observation, field observation, dusun stand measurement, and focus group discussion (FGD). The results of this study showed that Rumahkay community had for generations categorized their forest and regulated the rights of ownership and their utilizations through institutional development such as sasi negeri and kewang based upon mata rumah i.e. mata rumah anakele, anauweng, and anarete. While Sasi Gereja complemented kewang institution to be very effective in rules enforcement based on understanding, trust, and obedience. Overall, the strong local institution had been able to enhance the performance of dusun as shown by the vegetation density in dusun dati, dusun negeri, dusun pusaka, and dusun parusahaan.